Early effects of first‐line treatment with anti‐interleukin‐6 receptor antibody tocilizumab for chronic active antibody‐mediated rejection in kidney transplantation. Issue 8 (16th June 2020) - Lavacca, Antonio; Presta, Roberto; Gai, Chiara; Mella, Alberto; Gallo, Ester; Camussi, Giovanni; Abbasciano, Isabella; Barreca, Antonella; Caorsi, Cristiana; Fop, Fabrizio; Messina, Maria; Rossetti, Maura; et al.
Abstract: Introduction: Chronic active antibody‐mediated rejection (cAMR) is a major determinant of late allograft failure. Rituximab/immunoglobulins (IVIg) + plasma exchange (PLEX) showed controversial results in cAMR treatment. Tocilizumab (TCZ), a humanized anti‐interleukin 6 receptor antibody, has been recently used as rescue therapy in patients non‐responsive to rituximab/IVIg/PLEX with favorable outcomes. Whether TCZ acts "per se" or requires a priming effect from previous treatments is currently unknown. Methods: Fifteen patients with cAMR were treated with TCZ as a first‐line therapy and followed for a median time of 20.7 months. Results: Despite the majority of patients experiencing advanced transplant glomerulopathy (TG) at diagnosis (60% with cg3), glomerular filtration rate and proteinuria stabilized during the follow‐up, with a significant reduction in donor‐specific antibodies. Protocol biopsies after 6 months demonstrated significant amelioration of microvascular inflammation and no TG, C4d deposition, or IF/TA progression. Gene‐expression and immunofluorescence analysis showed upregulation of three genes (TJP‐1, AKR1C3, and CASK) involved in podocyte, mesangial, and tubular restoration. Conclusion: Tocilizumab adopted as a first‐line approach in cAMR was associated with early serological and histological improvements and functional stabilization even in advanced TG, suggesting a role for the use of TCZ alone with the avoidance of unnecessary previous immunosuppressants.